Post-Pandemic Hotel Decision Criteria Analysis Using Decision Making Methods - Prima Melati Sukma; Cutifa Safitri (Faculty of Computer Science (FILKOM) Brawijaya University, 2022)
This paper proposes an optimized hybrid process of the Analytic Hierarchy Process with the Simple Additive Weighting method for hotel decision-making. This study is important as many sectors including tourism are striving in the post-pandemic era. The proposed hypothesis is proven through a study case of hotel selection which included four factors for the criteria in decision-making, namely price, facilities, class, and location. The supported literature review on the topic described both methods are still widely used for the decision-making process. This study critically analyzed the importance of the selected factors. The superiority of this approach is to measure the validity by considering the depreciated value. To validate our findings, a group of sampling is done by performing the hybrid methods. Calculated results revealed the proposed methods achieve the decision-making process, the hybrid AHP – SAW model was found to be an effective method for assessing the hotel selection process.